2014
DOI: 10.5812/ircmj.12607
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing the Determinants of Social-health Inequality in Iran: A Multiple Attribute Decision Making Application

Abstract: Background:One of the main challenges of healthcare systems of developing countries is health inequality. Health inequality means inequality in individuals’ ability and proper functioning, resulting in inequality in social status and living conditions, which thwarts social interventions implemented by the government.Objectives:This study aimed to determine and prioritize the social determinants of health inequality in Iran.Materials and Methods:This was a mixed method study with two phases of qualitative and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…The results of Aghapoor and Mesri's study (2012) on the effects of social and cultural factors on the soldiers' quality of life showed that their quality of life was affected by their religious orientation, the duration of the military service, self-esteem, age, education, and housing conditions [ 29 ]. The results of many studies conducted on the civilians' SDH have proven the effects of economic, social, and public policies, as well as the culture and social values on health [ 25 , 30 , 32 , 48 ], which are consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results of Aghapoor and Mesri's study (2012) on the effects of social and cultural factors on the soldiers' quality of life showed that their quality of life was affected by their religious orientation, the duration of the military service, self-esteem, age, education, and housing conditions [ 29 ]. The results of many studies conducted on the civilians' SDH have proven the effects of economic, social, and public policies, as well as the culture and social values on health [ 25 , 30 , 32 , 48 ], which are consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…The results of Hassanzadeh and colleagues' study (2013) indicated that the prerequisites for health equity were the social factors and the alimentation of inequalities in the social classes [ 31 ]. The results of Zaboli and colleagues' study (2014) confirmed the suitability of using the conceptual framework of social determinants of health, developed by WHO, for investigating the social determinants and health inequalities in Iran [ 32 ]. Most of the recent studies have been conducted on the effects of social determinants of health based on the WHO framework.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Zaboli and colleagues reviewed and prioritized SDH in Iran. They believe, socio-economic status, living facilities such as housing, and social integrity had the greatest effect on decreasing health inequality in Iran (27). Addressing SDH requires an understanding of the impact of macroeconomic policies and social policies on the health.…”
Section: Introductionmentioning
confidence: 99%